2017
DOI: 10.2147/ijn.s132780
|View full text |Cite
|
Sign up to set email alerts
|

High drug-loading nanomedicines: progress, current status, and prospects

Abstract: Drug molecules transformed into nanoparticles or endowed with nanostructures with or without the aid of carrier materials are referred to as “nanomedicines” and can overcome some inherent drawbacks of free drugs, such as poor water solubility, high drug dosage, and short drug half-life in vivo. However, most of the existing nanomedicines possess the drawback of low drug-loading (generally less than 10%) associated with more carrier materials. For intravenous administration, the extensive use of carrier materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
268
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 416 publications
(295 citation statements)
references
References 215 publications
(206 reference statements)
5
268
1
Order By: Relevance
“…In order to better understand the intrinsic differences between these two nanomedicine candidates, comparative Raman studies were carried out at pH 7.0 and 4.0 in order to follow the PTX and DTX release under a range time(from 1 to 96 h) (Figures S1A and S2A, Supporting Information). Previously, other authors have demonstrated spectroscopical differences and variation of chemical conformation during drug release profiles . Thus, PTX IN‐PEG‐AuNPs and DTX IN‐PEG‐AuNPs were characterized by Raman spectroscopy after incubation for 96 h in PBS at 37 °C in order to (1) confirm the drug release and (2) to evaluate variations in the chemical orientation of PTX and DTX at pH 4.0 (when PTX and DTX are protonated) and pH 7.0 (when PTX and DTX are partially deprotonated).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to better understand the intrinsic differences between these two nanomedicine candidates, comparative Raman studies were carried out at pH 7.0 and 4.0 in order to follow the PTX and DTX release under a range time(from 1 to 96 h) (Figures S1A and S2A, Supporting Information). Previously, other authors have demonstrated spectroscopical differences and variation of chemical conformation during drug release profiles . Thus, PTX IN‐PEG‐AuNPs and DTX IN‐PEG‐AuNPs were characterized by Raman spectroscopy after incubation for 96 h in PBS at 37 °C in order to (1) confirm the drug release and (2) to evaluate variations in the chemical orientation of PTX and DTX at pH 4.0 (when PTX and DTX are protonated) and pH 7.0 (when PTX and DTX are partially deprotonated).…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that effective DOX release was carried out at pH 4, with stability attained at AuNP diameter close to 20 nm in physiological pH. This strategy can be applied to any drugs possessing complexation ability, such as carboxylates, phosphonates, including anthracycline, alkaloid, and flavonoid . The particle size and pH‐responsive point of nano‐therapeutics are dependent on the complex combinations of polymer ligands, drug molecules, and center metal ions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the application of the drug delivery system, one of the important properties of the system is a large capacity of the drug loading [6]. One effort that can be done to improve the properties is modification through the crosslinking method.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of controlled drug delivery systems provides a great number of advantages compared to those of traditional drug‐dosage forms, for instance, enhanced efficiency and stability, diminished toxicity, reduced side effects and capability to administrate the delivery of drugs to the active site . Biocompatibility, biodegradability, low cytotoxicity, high drug‐loading capacity and ease to monitor pharmacokinetic release profiles are the most desirable features of an ideal drug delivery system …”
Section: Introductionmentioning
confidence: 99%